The vital roles of teamwork, leadership style and career commitment in unlocking teachers’ innovative behavior - Johari, Aduni; Abdul Wahat, Nor Wahiza; Ismail, Ismi Arif (2011)
Globalization, innovation and education are three important terms that are closely related to any developing country at present. Teaching profession is an essential component in developing knowledgeable human capital. This article focuses on a correlational study to identify the predictors of teachers’ innovative behavior in national secondary schools. The three factors that have predictive potential of teachers’ innovative behavior are teamwork quality, career commitment and supervisor’s leadership style. The study also explored the integration of social exchange theory and stage model of innovative behavior. A quantitative method was employed involving 125 teachers. Data were analyzed using descriptive and inferential statistics of Pearson product-moment correlation coefficient and Multiple Linear Regression. Some implications and recommendations are discussed at the end of the article.